Model calculation for energy loss in ion-surface collisions. - Miraglia, Jorge Esteban (2003)
The so-called local plasma approximation is generalized to deal with projectiles colliding with surfaces of amorphous solids and with a specific crystalline structure (plannar channeling). Energy loss of protons grazingly colliding with aluminum, SnTe alloy, and LiF surfaces is investigated. The calculations agree quite well with previous theoretical results and explain the experimental findings of energy loss for aluminum and SnTe alloy, but they fall short to explain the data for LiF surfaces.